Peltier as a Thermoelectric Generator from Household Waste - Agus Supranartha; I Wayan Dikse Pancane; Nengah Sunaya; I Gde Nyoman Sangka; I Nyoman Mudiana (Jurnal Penelitian Pendidikan IPA, 2025)
The Utilization of heat energy as a generator of electrical energy with micro capacity can be done by using thermoelectric elements. Conversion system with Thermoelectric Generator (TEG) elements can be generated from heat from burning waste. Based on the nature and advantages of the fuel components, this study is to study and develop a system according to the capabilities of the TEG components that can be designed into a super mini generator system, namely by converting heat from fire into electricity. The method used in this study is a system for converting heat energy into electricity. The heat from the fire will be used to recharge batteries such as HT batteries, flashlights, GPS and others. The input or input to the system is the heat from combustion. The input component itself is a converter, namely a peltier. The function of the peltier is to directly convert heat energy into electricity. The results of the study are an output of 3.7 V. This design uses the IC LM317 as a regulator to process the output voltage of the conversion system. The purpose of regulation is so that the battery does not overcharge and is damaged.